Antifertility efficacy of methanolic root extract of Persicaria hydropiper on ovarian and uterine histomorphometry of female albino mice - Anjumani Ojah, Mridul Kumar Borthakur, Jogen Chandra Kalita (Journal of Applied Pharmaceutical Science, 2022)
The objective of the study was to validate the antifertility effect of Persicaria hydropiper on the reproductive physiology in female albino mice. Female albino mice were orally administered methanolic root extract of P. hydropiper at doses of 300 mg/kg body weight and 600 mg/kg body weight daily for 7 and 15 days and the effect on reproductive organs’ weight and histomorphometry was investigated. In the positive control group, 17β-estradiol (E2) (1 μg/kg body weight) was injected subcutaneously daily for 7 and 15 days. Persicaria hydropiper significantly reduced ovary and uterus weight in a dose-dependent manner. Compared to the control, the number of developing follicles was significantly reduced with significantly increased atretic follicles and the presence of pyknotic granulosa cells in the ovary of P. hydropiper root extract-treated mice. Histomorphometric changes in the uterine tissue of the extract-treated mice include reduction in endometrial thickness, height of luminal epithelium, diameter of the lumen, and number of endometrial glands. The results of the present study reveal that P. hydropiper causes atrophy in the uterine tissue and disrupts folliculogenesis that may be responsible for the reduced number of Graafian follicle and corpus luteum and increased atretic follicles, thereby rendering an antifertility effect.
Keywords: Antifertility, Atresia, methanolic root extract, mice, Persicaria hydropiper